THE INFLUENCE OF SOCIAL SKILLS ON LONELINESS IN ADOLESCENTS - Aam Imaddudin (Study Program Guidance and Counseling, Univesitas Pendidik, 2023)
This research is motivated by a growing phenomenon among adolescents related to social skills and loneliness. This study aims to determine the effect of social skills on loneliness in adolescents at MAN 2 Tasikmalaya. The sample comprised 257 students of class XI and class XII at MAN 2 Tasikmalaya. This research sample uses a probability sampling technique. The data collection instrument used a social skills scale and a loneliness scale. The social skills scale uses 5 aspects taken from (Anhar, 2014). The loneliness scale has 4 parts, namely feelings of severe loneliness, having feelings with certain situations, losing friendships, and feelings of having a meaningful relationship. The approach used in this research is descriptive quantitative using a linear regression test through SPSS version 25. Based on the study's results, it was found that social skills did not affect loneliness in adolescents at MAN 2 Tasikmalaya with an R square value of 0.003.